Feasibility study and design of cherenkov-type detectors for measurements of fast electrons within tokamaks - Jakubowski, L.; Rabiński, M.; Stanisławski, J.; Sadowski, M.J.; Żebrowski, J. (Вопросы атомной науки и техники, 2007)
The paper presents feasibility and design studies of the Cherenkov-type detectors designed for measurements of energetic electrons within tokamak devices. The technique in question enables the identification of electron beams, the determination of their spatial distribution, as well as the measurements of their temporal characteristics. On the basis of the presented analyses, i.e. heat transfer studies, a prototype of the Cherenkov measuring head has been designed, constructed and tested within CASTOR tokamak. Obtained experimental results demonstrated that relatively intense Cherenkov signals appear particularly during the final phase of the discharge, when the expanding plasma column reaches the detector.